Production of Hydrogen from Ethanol Steam Reforming Over Ni-Mn/La2O3-ZrO2 Catalyst - Wu*, Hongda; Yin, Yu; Liu, Hanzhi; Liu, Tianshi; Zhao, Lue (Asian Journal of Chemistry, 2014)
La2O3-ZrO2 composite oxide support was prepared by oxalate precipitation method and Ni-Mn/La2O3-ZrO2 catalysts were prepared by impregnation. The catalysts were characterized by means of X-ray diffraction, temperature programmed reduction and temperature programmed oxidation. The performance of catalysts in steam reforming of ethanol was studied and the effects of the catalyst composition on catalytic activity and selectivity were discussed. The results showed that Ni-Mn/La2O3-ZrO2 catalyst was remarkable tetragonal phase, nickel species and manganese species were highly dispersed on the support surface. The Ni active component existed as zero valent in catalysts while Mn active component existed as MnO during steam reforming of ethanol and synergy existed between nickel and manganese species; (8Ni1Mn)4(2La8Zr) catalyst exhibited the best catalytic performance in steam reforming of ethanol, with which ethanol conversion rate was 100 % in the situation of 823 K and CO content was lower at high temperature. A certain amount of carbon deposition was observed on all Ni-Mn/La2O3-ZrO2 catalysts in steam reforming of ethanol.